Analysis of near wall combustion and pollutant migration after spray impingement. (October 2019) - Ma, Tianyu; Feng, Lei; Wang, Hu; Liu, Haifeng; Yao, Mingfa
Highlights: Unstable flame after spray impact is found with the decrease of ambient temperature. Enlarged high temperature area help accelerate film evaporation and combustion. Wall temperature and impact angle show different effects in near wall combustion. Abstract: Spray impingement has aroused more and more interests in recent years with the increase of injection pressure in internal combustion engines. In this paper, the near wall combustion after fuel spray impingement is studied based on an updated film development model and experiment in constant volume vessel. Relationship between spray injection and flame development under different ambient temperature is analyzed as well as the near wall distribution of combustion products. In the first part, a mathematical model that considered the effects of surface tension on spray impingement is built for better prediction of film development. Reasonable results are obtained at room temperature spray impingement case, and the split distribution of film depth is also well captured. In the second part, flame development in the near wall region is investigated based on the proposed numerical model and experiments. The result shows that the flame becomes circumferentially nonuniformed at lower ambient temperature (723 K) and the evolution of downstream flame become sensitive to the wall temperature. At lower ambient temperature (723 K), increasing wall temperature could enlarge the high temperature zone, which is helpful to accelerate the film evaporation and soot oxidation. At higher ambient temperature condition, the spray impact angle should be reduced to create more concentrated combustion (stronger stratification), which could improve the combustion efficiency in the near wall region.